2011
DOI: 10.1111/j.1755-3768.2009.01676.x
|View full text |Cite
|
Sign up to set email alerts
|

Refractive errors in children and young adults with Down’s syndrome

Abstract: The incidence of refractive errors in Macedonian children and young adults with DS was similar to that in Asian children. Compared with White (Caucasian) and Asian children with DS, Macedonian children and young adults exhibited lower incidences of hypermetropia and myopia, and a higher incidence of astigmatism, in which oblique astigmatism represented the predominant type.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
18
2
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(26 citation statements)
references
References 19 publications
5
18
2
1
Order By: Relevance
“…This finding was consistent with previous studies with Asian children 20. Earlier studies suggested the prevalence of astigmatism increased with age 21.…”
Section: Discussionsupporting
confidence: 93%
“…This finding was consistent with previous studies with Asian children 20. Earlier studies suggested the prevalence of astigmatism increased with age 21.…”
Section: Discussionsupporting
confidence: 93%
“…Our finding on hyperopia (9.5%) is comparable to other studies with a reported range of between 12%26 and 15%,22 but lower than reports by other authors 19,29,30,40. Our finding of 28.6% prevalence of astigmatism is similar to the findings in other studies,19,20,22,25,26,29,38,42 although lower than findings reported by other authors 17,24,40. The high incidence of refractive errors among children with DS is believed to be caused by failure of emmetropisation 39,34.…”
Section: Discussionsupporting
confidence: 88%
“…Previous studies7–19 have established that refractive errors and strabismus are more prevalent among children and young adults with DS when compared with controls, as reported in other studies 17,23,24,38,39. For refractive errors, our finding of 38.1% prevalence of myopia (Table 1) is comparable to findings from other studies17,23,24,38,39 and lower than findings by other authors,17,24,39 although higher than findings reported by others 19,27,35,40. In children with DS, heart defects have been reported to be associated with myopia, although the mechanism is not clear 22,27,41.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations